Influence of different herbicides on weed suppression, forage yield and economics of berseem (Trifolium alexandrinum) - Kumar, Sunil; Dhar, Shiva (The Indian Journal of Agricultural Sciences, 2008)
A field experiment was conducted during winter (rabi) season 2000-01 to 2002-03 at Jhansi to find out suitable herbicides for productivity enhancement by suppression of associated weeds. like Chicorium intybus L. along with other weed flora in berseem (Trifolium alexandrinum L.). Eight herbicides, namely butachlor @ 1.0 and 2.0 kg ai/ha as pre- emergence, trifluralin @ 0.60 and 1.20 kg ai/ha as pre-plant incorporation, fluchloralin (30.60 and 1.20 kg ai/ha pre-plant incorporation and imazethapyr @ 0.10 and 0.15 kg ai/ha pre-emergence were tested along with common salt treatment (10%) and unweeded control (weedy check). Among herbicides, imazethapyr @ 0.10 and 0.15 kg ai/ha was significantly superior in controlling C.intybus along with the other weeds (weed control efficiency 74.2%). Significantly higher forage(88.2 tonnes/ha), crude protein yield (2.6 tonnes/ha) and benefit : cost ratio (1.86) was recorded with application of imazethapyr @ 0.10 kg ai/ha pre-emergence to berseem than the other treatments.